Discovery of new inhibitor for the protein arginine deiminase type 4 (PAD4) by rational design of α-enolase-derived peptides. (June 2021) - Ahmad Nadzirin, Izzuddin; Chor, Adam Leow Thean; Salleh, Abu Bakar; Rahman, Mohd Basyaruddin Abdul; Tejo, Bimo A.
Highlights: Protein arginine deiminase type 4 (PAD4) is identified as being responsible for pathogenesis of rheumatoid arthritis. PAD4 converts the arginine residue to citrulline in certain proteins, which subsequently act as autoantigens that stimulate antibody production. We discovered a peptide with a better inhibitory activity against PAD4 compared to existing PAD4 inhibitors such as MTX and streptomycin. Abstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease affecting about 0.24 % of the world population. Protein arginine deiminase type 4 (PAD4) is believed to be responsible for the occurrence of RA by catalyzing citrullination of proteins. The citrullinated proteins act as autoantigens by stimulating an immune response. Citrullinated α-enolase has been identified as one of the autoantigens for RA. Hence, α-enolase serves as a suitable template for design of potential peptide inhibitors against PAD4. The binding affinity of α-enolase-derived peptides and PAD4 was virtually determined using PatchDock and HADDOCK docking programs. Synthesis of the designed peptides was performed using a solid phase peptide synthesis method. The inhibitory potential of each peptide was determined experimentally by PAD4 inhibition assay and IC50 measurement. PAD4 assay data show that the N-P2 peptide is the most favourable substrate among all peptides. Further modification of N-P2 by changing the Arg residue to canavanine [P2 (Cav)] rendered it an inhibitor against PAD4 by reducing the PAD4 activity to 35 % with IC50 1.39 mM. We conclude that P2 (Cav) is a potential inhibitor against PAD4 and can serve as a starting point for the development of even more potent inhibitors.